Civil Disobedience for Conflict Resolution: Gandhi and Thoreau - Poudyal, Phatik Prasad (Literary Studies, 2015)
The importance of civil disobedience in conflict resolution and peace negotiations has been universally recognized after the second half of the twentieth century. Civil disobedience as a powerful tool to fight the social and political injustices was first forwarded by Henry David Thoreau, an American philosopher and writer, in his acclaimed essay “On the Duty of Civil Disobedience” published in 1849. Though Thoreau’s practice of this idea transported significant changes while fighting the unjust American Government in his time, the power and significance of civil disobedience was fully realized after Mahatma Gandhi practiced it to fight the powerful British Empire in Africa and India. Though it seemed in the outset almost impossible to defy such a powerful enemy without using weapons or any other means of violence, Gandhian struggle surprised the world with the notion that the peaceful protest done in the ground of morality and truth has an immense power in comparison to physical force. This political theory of Gandhi provides us with the way to see and arbitrate conflict in the moral ground. His vision also provides us a realistic understanding of socio-political issues than any other conflict resolution theories of the contemporary time.